E-Book Innovation Based on the REACT Learning Model to Improve the Communication Skills of Elementary School Teacher Education Students - Eko Sucahyo; Rani Ningtyas; Sabri Sabri (Universitas Negeri Semarang, 2025)
This study aims to develop an E-Book based on the REACT learning model (Relating, Experiencing, Applying, Cooperating, Transferring) to improve the communication skills of elementary teacher education (PGSD) students. The research adopted the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). At the analysis stage, students’ needs and profiles were identified. The design stage focused on structuring the E-Book integrated with the REACT syntax. The development stage produced a prototype validated by experts. Implementation was carried out through limited and field trials using a One Group Pretest–Posttest design. The limited trial involved 15 PGSD students, while the field (wider) trial was conducted with 40 students. Evaluation was conducted both formatively and summatively. Validation results showed an average score of 88.25% (valid category). The paired sample t-test indicated sign. (2-tailed) = 0.000 < 0.05, proving a significant difference in communication skills before and after using the E-Book. Moreover, the comparison test yielded to count = 11.915 > ttable = 1.684, confirming a meaningful improvement. In conclusion, the REACT-based E-Book developed through the ADDIE model is valid, practical, and effective in enhancing the communication skills of PGSD students and is recommended for wider application in higher education.